Penggunaan Kecerdasan Buatan dalam Menunjang Pengajaran Guru Agama Kristen - Wardi Wardi (Departemen Literatur dan Media, Sekolah Tinggi Teologi Arrabona Bogor, 2024)
The use of artificial intelligence in the context of Christian religious teaching is an important innovation that has the potential to increase the effectiveness and efficiency of learning. The background to the problem reflects the need to update Christian religious teaching methods to face the demands of technological developments. The research method used involves collecting qualitative data through observation, and implementing AI technology in the teaching process. The aim of this research is to evaluate the impact of using AI in supporting teachers' teaching of Christianity, analyze student responses, and investigate changes in their understanding and participation in Christian religion learning. The research results show that the application of AI can increase student engagement, personalize learning, and provide faster feedback to teachers. The implications of this research detail the concrete benefits of using AI in enhancing Christian religious learning experiences, while highlighting the challenges that may be faced in its application in religious education settings. This study contributes to further understanding of the potential of AI technology in improving Christian religious teaching methods in the digital era.